MODULATION OF APOPTOSIS AND IMMUNE RESPONSE BY SYNBIOTIC IN EXPERIMENTAL COLORECTAL CANCER - ANGELA VERMA; GEETA SHUKLA (International Journal of Pharma and Bio Sciences, 2015)
The study was designed with an aim to delineate the apoptotic and immunomodulating potentials of synbiotic (L.rhamnosus + L.acidophilus + inulin) in experimental colon carcinogenesis. Ten groups of Sprague Dawley rats received either probiotic, prebiotic or synbiotic for 18 weeks along with the inducement of tumors by DMH. It was found that synbiotic administration to DMH -treated animals promoted apoptosis in colonic tumors by down regulating Bcl-2, K-ras expression and enhancing the expression of wild type P53 compared with the tumors of DMH-only-treated animals. Immunologically, the colonic tissue of synbiotic +DMH -treated animals had significantly increased levels of TNF-α, IFN- γ and IL-10 (p<0.05) while IL-6 level decreased compared with DMH-only-treated animals. The synbiotic administration promoted apoptosis in the colonic tissues by modulating the gene expression and cytokine levels, suggesting the prophylactic potentials of synbiotic against colon cancer.